MEMBANGUN RELATIONSHIP DENGAN DUNIA USAHA/ DUNIA INDUSTRI SEBAGAI STRATEGI KOMUNIKASI PEMASARAN (STUDI KASUS DI SMK PELITA 2 BANDUNG) - Wahyudi Prasasti (Universitas Islam Negeri Imam Bonjol Padang, 2020)
SMK Pelita 2 Bandung is a private school in Indonesia, West Java. SMK Pelita 2 Bandung managed to cooperate together with the business world/world industry. In building relationships with the business world/Industrial World SMK Pelita 2 not only works just like other SMK. Appropriate marketing communication strategy is required therein. Therefore, SMK Pelita 2 Bandung implements integrated marketing communication in communicating and building relationships. The purpose of this research is to know the marketing communication strategy conducted by SMK Pelita 2 Bandung in establishing a relationship with the world of business/world. The study uses qualitative descriptive research methods with data collection through observation, interviews, and documentation studies. The theory used in this study was the integrated marketing theory of Communists. The results of this research is an integrated marketing communication instrument into a strategy used by SMK Pelita 2 Bandung in building relationships with the business world/industrial world. The marketing instruments are sales promotion, direct marketing, Public relations & Publicity, and personal sales. The process of marketing communication that SMK traversed varies according to the integrated Marketing communication instrument. Marketing communication strategy applied by SMK Pelita 2 Bandung shows success in building relationships with the business world/industrial world.